584 Evaluation of micro-RNA expression in cytological smears in women with low grade squamous intraepithelial lesions. (14th December 2020) - Prisyazhnaya, Tatyana; Malek, Anastasia; Knyazeva, Margarita; Berlev, Igor
Abstract : Introduction/Background: MicroRNAS are short molecules that regulate gene expression. The microRNA expression profile changes in cells during neoplastic transformation. In particular, characteristic changes in microRNA are observed in the cells of the cervical epithelium during the development of intraepithelial neoplasia. These changes are compounded in invasive cervical cancer cells. Accordingly, microRNAS can serve as diagnostic or prognostic biomarkers in patients with cervical dysplasia of varying severity. In this study, we analyzed microRNA in patients with low grade squamous intraepithelial lesions (LSIL) and compared the data obtained with the clinical course of the disease. Methodology: Total RNA was isolated from the epithelium of patients with low grade squamous intraepithelial lesions and divided into two pools: "persistence" (n=10) and "recovery" (n= 10), depending on the data of repeated cytological examination conducted after 6–9 months. In the obtained samples, we performed a comprehensive screening analysis of 85 micro-RNA expression (Cancer focus miRCURY RT-PCR panel, Exiqon, Denmark). Results: The results of microRNA profiling showed different levels of expression of 9 molecules in the compared groups. In cases of persistent cervical epithelial atypia during dynamic observation, miR-126-3p Mir-16-5p miR-182-5p miR-200c-3p, miR-205-5p, miR-223-3p, miR-24-3p molecules were expressed significantly more actively than in the group of samples obtained from patients whose cervical epithelium condition normalized during observation. The reverse situation was observed for miR-192-5p and miR let-7f-5p. Conclusion: MicroRNA molecules whose expression level correlates with the prognosis of cervical epithelial dysplasia can serve as useful biomarkers and be used to personalize the treatment of this common gynecological disease. Validation of the microRNA estimation method requires more extensive research. Disclosures: The authors declare no conflict of interest. The funders had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript, or in the decision to publish the results.